2022
DOI: 10.3389/fvets.2022.838457
|View full text |Cite
|
Sign up to set email alerts
|

Fijian Farmers' Attitude and Knowledge Towards Antimicrobial Use and Antimicrobial Resistance in Livestock Production Systems–A Qualitative Study

Abstract: Antimicrobial resistance (AMR) is a global health issue affecting humans and livestock. To mitigate AMR risks, responsible use of antimicrobials in livestock production systems have been advocated. Studies have reported patterns of antimicrobial use (AMU) in livestock production systems; however, there is limited information on the drivers of AMU and AMR. Therefore, this study aimed to explore and understand the attitude and knowledge of Fijian livestock farmers on AMU and AMR. Livestock farmers and managers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…There is therefore a greater chance of incorrect clinical diagnosis and use of antimicrobials when compared to clinical diagnosis and treatment by a veterinarian in the field ( 30 ). The current approach could set a precedence that self-diagnosis and self-prescribing of antimicrobials by Fijian livestock farmers was acceptable and the norm in everyday livestock production and management despite findings from our previous study demonstrating that farmers lacked knowledge and understanding of AMU and AMR ( 16 ). These practices may further aggravate and create obstacles for the implementation of behavioral interventions to safeguard AMU.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…There is therefore a greater chance of incorrect clinical diagnosis and use of antimicrobials when compared to clinical diagnosis and treatment by a veterinarian in the field ( 30 ). The current approach could set a precedence that self-diagnosis and self-prescribing of antimicrobials by Fijian livestock farmers was acceptable and the norm in everyday livestock production and management despite findings from our previous study demonstrating that farmers lacked knowledge and understanding of AMU and AMR ( 16 ). These practices may further aggravate and create obstacles for the implementation of behavioral interventions to safeguard AMU.…”
Section: Discussionmentioning
confidence: 80%
“…This present study and our earlier study also alluded to the supply chain issue related to medicines where only a limited range of antimicrobials was available for use ( 16 ). The findings are consistent with those reported by Dione et al ( 55 ) in Uganda where supply chain constrains were identified as potential drivers of inappropriate AMU ( 55 ).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations